2015
DOI: 10.4103/0972-3919.158528
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of fluorodeoxyglucose positron emission tomography/computed tomography in pyrexia of unknown origin

Abstract: Purpose of the Study:The present study was undertaken to evaluate the diagnostic utility of fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT) in patients presenting as pyrexia of unknown origin (PUO).Materials and Methods:Forty-seven patients (31 males and 16 females; mean age of 42.7 ± 19.96 years) presenting as PUO to the Department of Medicine at the All India Institute of Medical Sciences, New Delhi over a period of 2 years underwent F-18 FDG PET/CT. PET ⁄ CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…The percentage of patients diagnosed with malignancies in our study was quite low (16%), similar to that observed in many previous studies [ 21 , 27 , 28 , 32 ], which could be explained by the widespread early use of cross-sectional imaging (ultrasound CT, MRI) resulting in a reduction of cases of malignancies presented as FUO. Non-Hodgkin’s lymphoma was the most common malignant cause of FUO in our study, as in previous studies [ 27 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The percentage of patients diagnosed with malignancies in our study was quite low (16%), similar to that observed in many previous studies [ 21 , 27 , 28 , 32 ], which could be explained by the widespread early use of cross-sectional imaging (ultrasound CT, MRI) resulting in a reduction of cases of malignancies presented as FUO. Non-Hodgkin’s lymphoma was the most common malignant cause of FUO in our study, as in previous studies [ 27 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…18 F-FDG, as a non-specific indicator of increased glycolytic metabolism, is concentrated not only in infectious sites but also in NIID and in neoplasms, all being possible causes of FUO. Several studies support the use of 18 F-FDG-PET in the assessment of FUO [ 12 , 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 32 , 33 , 34 , 35 , 36 , 37 ]. Moreover, an abnormal 18 F-FDG-PET/CT scan, as part of a structured diagnostic protocol for FUO, has been shown to be among the significant predictors for reaching a diagnosis [ 32 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[ 1 2 ] In a study in an Indian setting, the overall estimated rate was found to be 38%,[ 9 ] akin to the reported literature. The major advantage can be observed in investigating NIID,[ 6 7 8 9 10 11 12 ] which is in recent times one of the single most identifiable causes of PUO and relatively unaddressed by the morphological cross-sectional imaging modalities. Particularly in situations such as vasculitis, metabolic FDG-PET/CT demonstrates great promise not only from diagnosis but also from the treatment monitoring viewpoint.…”
mentioning
confidence: 99%